(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Let G be a finite, simple, undirected and non-trivial graph. A fuzzy graph is said to admit tri-magic labeling if the number of magic membership values Ki’s and Kj’s (1 ≤